Pengaruh Strategi Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Toko Kosmetik Ve Beauty di Denpasar - Diantary, Ni Luh; Susanti, Putu Herny; Diputra, Gde Indra Surya (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Promotion strategy and service quality are suspected to influence the purchasing decisions at VE Beauty Cosmetic Store in Denpasar. The research problem and objectives aim to determine the impact of promotion strategy and service quality on purchasing decisions at VE Beauty Cosmetic Store in Denpasar. The study involved 6976 consumers, with a sample size of 99 people selected using accidental sampling. Data was collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The analysis results indicate that: 1) promotion strategy has a positive and significant influence on purchasing decisions at VE Beauty Cosmetic Store in Denpasar, 2) service quality has a positive and significant influence on purchasing decisions at VE Beauty Cosmetic Store in Denpasar, 3) product quality and service quality together have a positive and significant influence on purchasing decisions at VE Beauty Cosmetic Store in Denpasar. Recommendations to improve consumer purchasing decisions at VE Beauty Cosmetic Store in Denpasar include providing fast service, prioritizing customer comfort, regularly updating activities and offers on websites and social media, evaluating employee performance, and providing training to improve employees’ knowledge of the offered products.